How Do High and Low Anxious FL Listeners Employ FL Listening Comprehension Strategies? Exploring Student Perspectives - Gizem Berber; Safiye İpek Kuru Gönen (Anı Publishing, 2017)
There has been a growing body of research on the relationship between foreign language (FL) listening anxiety and FL listening comprehension strategy use; however, how these strategies are employed by learners with different listening anxiety levels is an area open to investigation. Based on such need, this study aimed at exploring FL listening comprehension strategies used by high and low anxious FL listeners in a Turkish EFL context. For this purpose, 15 high anxious and 13 low anxious listeners at a Turkish university kept reflective journals for five weeks and participated in semi-structured interviews. The qualitative data were analyzed according to the steps of Content Analysis. Findings revealed that both high and low anxious students employed various listening strategies, i.e., cognitive and metacognitive strategies, while listening in the target language. However, high and low anxious listeners differed in the ways they implemented some of the specific strategies such as note-taking, translation, directed attention, and real time assessment. The results of the study proposed implications for FL listening comprehension strategy use and strategy training in relation with FL listening anxiety.